Design of AlGaN/AlN Dot‐in‐a‐Wire Heterostructures for Electron‐Pumped UV Emitters. Issue 7 (13th November 2019) - Dimkou, Ioanna; Harikumar, Anjali; Ajay, Akhil; Donatini, Fabrice; Bellet-Amalric, Edith; Grenier, Adeline; den Hertog, Martien I.; Purcell, Stephen T.; Monroy, Eva
Abstract : This article describes the fabrication of nitrogen‐polar Al x Ga1− x N/AlN ( x  = 0, 0.1) quantum dot (QD) superlattices (SLs) integrated along GaN nanowires (NWs) for application in electron‐pumped UV sources. The NWs are grown using plasma‐assisted molecular beam epitaxy on n‐type Si(111) wafers using a low‐temperature AlN nucleation layer. Growth conditions are tuned to obtain a high density of noncoalesced NWs. To improve the uniformity of the height along the substrate, the growth begins with a long (≈900 nm) NW base, with a diameter of 30–50 nm. The Al x Ga1− x N/AlN active region is 400 nm long (88 periods of QDs), long enough to collect the electron–hole pairs generated by an electron beam with an acceleration voltage ≤5 kV. The spectral response is tuned in the 340–258 nm range by varying the dot/barrier thickness ratio and the Al content in the dots. Internal quantum efficiencies as high as 63% are demonstrated. Abstract : This article describes the fabrication of AlGaN/AlN quantum dot (QD) superlattices (SLs) on GaN nanowires (NWs) for application in electron‐pumped UV sources. The emission is tuned in the 340–258 nm range by varying the dot/barrier thickness ratio and the Al content in the dots.